Comparative study of a GEM-based fast neutron detector using4HE/CO2and4HE/CO2/C4H10gas mixtures - Kiadtisak Saenboonruang (2018)
© 2017, Chiang Mai University. All rights reserved. 1H- or4He-contained gas mixtures are usually used to detect fast neutrons, which relies on elastic scattering between fast neutrons and light gas molecules. In this research, gas mixtures of4He/CO2(80:20 and 70:30) and4He/CO2/C4H10(70:23:7) were flowed through a 10 cm□ 10 cm triple-Gas Electron Multiplier (GEM) detector at a constant flow rate of 3.0 L/hr in order to detect fast neutrons. Comparisons of relative efficiencies, relative gains, and detection uniformity for all gas types were investigated by measuring signal counts and signal amplitudes. Results showed that a gas mixture of4He/CO2(80:20) had the highest relative efficiency and relative gains amongst all gas mixture types. In terms of detection uniformity, detection efficiency at the center of the active area was approximately 20% higher than areas close to the detector edges. Details of basic knowledge of GEM, experimental procedures, results and discussion are included in this article.